The Effect of Sustainable Packaging Aesthetic on Consumer Behavior: A Case Study from India - Urvi Kapse; Yogesh Mahajan; Manoj Hudnurkar; Suhas Ambekar; Rahul Hiremath (Australasian Accounting, Business and Finance Journal, 2023)
Sustainable packaging has opened new growth opportunities for the packaging industry in the Indian context. This research aims to understand whether sustainable packaging has helped enhance environmentalist consumer behavior and increased product sales. Packaging is essential to any food or non-food product since it protects the client from humidity, light, heat and other external factors. Packaging serves as a kind of communication and a means of drawing the attention of a company's final consumer. However, to meet modern environmental standards, it must preserve goods while remaining environmentally friendly. Consumers are becoming more aware of environmental concerns and their purchase habits' impact on the environment. Customers like to do business with ecologically conscientious organizations. In keeping with the study's goals, this paper uses a strategy for combing through current research studies on the impact of sustainable packaging aesthetics on customer behavior. A quantitative research design was adopted. The structured questionnaire was designed based on the literature study model as a guide. The study results show that Consumers prioritize price, quality, and brand over all other considerations. Based on these findings, investing in sustainable packaging at the expense of any other purchase criteria is likely to be a losing proposition.
Keywords: Sustainability; packaging; consumer behavior; environmental protection; green marketing; India